The role of green open spaces in the mental health and happiness of urban communities - Tanwir, Siti Saroh; Huda, Ahmad Syaiful; Latif, Abdul; Syafi’i, Ahmad (Journal of Placemaking and Streetscape Design, 2024)
Background: Mental health is the most important thing in human life, but in reality in Indonesia the level of mental health disorders is still high. People who live in urban areas are vulnerable to mental health disorders such as anxiety, stress and depression which are caused, among other things, by high work pressure and lack of recreational activities. Method: This article uses a non-experimental correlational method, collecting secondary data from various sources and journal articles without experimental manipulation. The focus is on urban communities. Findings: Difficulty accessing natural things, such as rural environments, even something "green". is one of the factors that makes urban residents easily experience depression. Depression can cause decreased energy, sleep disturbances, changes in appetite, and other physical problems, therefore fulfilling recreational needs that are cheap and easily accessible through public open spaces can be a solution to reduce people's stress levels. Conclusion: Green open space (RTH) provides an opportunity to escape from fatigue, work pressure, city crowds so that people can release their stress by immersing themselves in nature and connecting themselves with the natural environment. RTH has many positive benefits so its existence is very necessary, especially in densely populated residential areas. Novelty/Originality of this article: This study proposes a model for integrating green open space (GOS) into urban planning that considers physical aspects and therapeutic functions for mental health. This model combines evidence-based GOS design with community mental health programs, creating a 'green healing zone' that can be accessed and optimally utilized by city residents to reduce stress and improve mental well-being.